Selection of streptomyces chitinolytics for biocontrol of fungal phytopathogens - I. G. Shirokikh; N. A. Bokov; A. V. Bakulina; E. A. Bessolitsyna (Аграрная наука Евро-Северо-Востока, 2025)
Interest in chitinolytically active microorganisms is related to the possibility of their participation in protecting plants from fungal infections, since chitin is a structural component of fungal cell walls. Among the bacteria, the most active chitinolytics include representatives of the genus Streptomyces. The use of streptomyces in the fight against harmful phytopathogens of agricultural crops is due to the ability to synthesize a wide range of biologically active compounds, as well as environmental safety, since streptomyces are a natural component of any agrocenosis. The paper studied the distribution of streptomyces chitinolytics among natural isolates from the soils of the Vyatka-Kama Urals. Chitinolytically active cultures were screened using functional (phenotypic) and genetic predictors. The assessment of functional activity showed that the proportion of chitin-actively decomposing strains with an enzymatic index of EI≥2 was about 40 % in the studied soils. Strains of S. griseoaurantiacus and S. thermocarboxydus species decomposed chitin most actively. The genetic determinants of chitinolysis – the genes of chitinase A, chitinase C, and chitin-binding proteins – were determined in the genomes of natural isolates using PCR using specially developed specific primers. It has been established that individual genetic determinants of chitinolysis (chiA, chiC, chb) are much more widespread in streptomyces than chitinolysis detected in functional tests. This is due to the inducible nature of the chitinase enzyme and the dependence of its activity on exogenous factors. Chitinolysis of local isolates was compared with the activity of strains isolated from the soil of the arid zone. On the 7th day of growth of local isolates in the immersed culture, chitinase activity varied from 15.83±12.01 to 50.63±38.81 U/ml, whereas in the strain isolated from arid soil, the enzyme activity in the same period was 76.46±42.12 U/ml. Evaluation of the antifungal effect of streptomyces chitinolytics against pathogens of alternariasis, helminthosporiosis and fusarium root rot of grain crops revealed local strains promising for use in agrobiotechnology.